The German minority issues in the context of changes the strength from the perspective of 25 years official existence this national minority in Poland = Problematyka mniejszości niemieckiej w kontekście zmian stanu liczebności z perspektywy 25 lat oficjalnego istnienia tej mniejszości narodowej w Polsce - Popieliński, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author presents estimations the polish and german scientists and various official estimates of the strength of the German minority, especially the results of the Polish National Census 2002 and 2011. He answers on the leading question: Why decreasing the strength of the German minority in our country? The author has listed and described the most important factors that have influence on the strength of the minority.
Keywords: the German minority; size of the German minority in Poland; the German minority organizations; censuses 2002 and 2011 in Poland; Upper Silesia; Silesians; mniejszość niemiecka; liczebność mniejszości niemieckiej w Polsce; organizacje mniejszości niemieckiej; spisy ludności w 2002 i 2011 r. w Polsce; Górny Śląsk; śląskość